Pengaruh Model Pembelajaran RADEC Berbantuan Video Animasi Warisan Budaya terhadap Kemampuan Literasi Budaya Siswa Sekolah Dasar: The Effect of the RADEC Learning Model Assisted by Cultural Heritage Animation Videos on the Cultural Literacy Skills of Elementary School Students - Debi Servinta Br Perangin-angin; Surya Dharma; Hapni Laila Siregar; Yakobus Ndona; Noni Rozaini; R Mursid (ITScience (Information Technology and Science), 2026)
21st-century education emphasizes student-centered learning that develops various competencies, including cultural literacy. The low level of cultural literacy among elementary school students indicates that existing models and supporting media have not effectively developed this competence. The RADEC learning model, supported by cultural heritage animation videos, is expected to serve as an alternative for creating learning experiences that are more active, contextual, and meaningful. This study aims to analyze the impact of the RADEC learning model—supported by cultural heritage animation videos—on elementary school students' cultural literacy skills. A quasi-experimental, non-equivalent group design was employed, and data were analyzed using SPSS version 25.0. A cultural literacy skills questionnaire served as the research instrument. The results indicate: (1) a significant effect of the RADEC learning model (supported by cultural heritage animation videos) on students' cultural literacy skills, with a Sig. (2-tailed) value of 0.000 (< 0.05). The average N-Gain score for the experimental class—which received the RADEC learning model treatment supported by cultural heritage animation videos—was 56.4603 (or 56.5%). These results demonstrate that implementing the RADEC learning model supported by cultural heritage animation videos effectively enhances students' cultural literacy skills. Furthermore, the Independent-Samples T-Test results (Sig. 2-tailed = 0.000 < 0.05) confirm the model's significant impact on cultural literacy skills. At the same time, the average N-Gain score of 56.4603 (56.5%) indicates the model's effectiveness in improving these skills.